A influência da Aprendizagem Baseada em Problemas no desempenho dos estudantes de Administração na disciplina de Contabilidade Empresarial - HERNANDES, Dayane de Oliveira Pinto Silva (2023)
This dissertation is linked to the line of research “Training and action of teaching professionals and educational practices” of the Postgraduate Program in Education – PPGE at Universidade do Oeste Paulista – UNOESTE. It is understood that the use of the Aprendizagem Baseada em Problemas – ABP or Problem-Based Learning – PBL methodology will assist the teacher in his teaching practice and facilitate the teaching and learning process of students, promoting autonomy in teaching and participation between peers. The research aimed to promote collaboration among Administration students among their peers, the development of knowledge, skills and attitudes through problem solving in the Business Accounting discipline using the ABP methodology on the “Be Active” platform. The general objective of the research was to analyze how the use of the ABP methodology, through the “Be Active” platform, can promote collaboration between students and the development of their knowledge, skills and attitudes in the Business Accounting discipline of the Administration course, with the aim of improving the teaching and learning process. It also proposed to identify the possible difficulties and benefits that teachers may encounter when implementing PBL through a digital platform in the Business Accounting discipline; analyze how PBL contributes to the construction of students' knowledge, skills and attitudes in the context of the Business Accounting discipline; describe students' perception of the effectiveness of the ABP methodology using the “Be Active” platform in facilitating learning and promoting collaboration; and examine how the use of ABP on the "Be Active" platform influences student engagement and participation during Business Accounting classes. It presented as methodological procedures, research with a qualitative and interventional approach. The following research instruments were used: 1) participant observation; 2) collection of documents; 3) application of questionnaires: 3.1) Free Word Association Test – TALP, 3.2) Kolb Learning Style Inventory, 3.3) Questionnaire on ABP. To analyze the data collected through the research instruments, techniques were used to favor triangulation: Similitude Analysis, Discursive Textual Analysis – ATD, Prototypical Analysis for data collected using the TALP technique and Analysis of crossings between variables. However, it was found that the PBL methodology, using the “Be Active” platform, proved to be effective in promoting the development of attitudes and skills in students. The majority of participants reported having acquired and improved specific entrepreneurial skills through this methodology.